Procedures Of Development Of The Curriculum Of The Education Of Adult Children In Humanistic Approach - Hijriyani, Yuli Salis (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2024)
The role of parents, alpha, generation alpha offered to students by educational institutions (sekolah). Students engage in various learning activities in accordance with the educational programmes, which encourage growth and development in line with educational goals that have been set. With the existence of this research is able to reveal the ease of the procedure of developing curricula with a humanistic approach. This research uses a kind of qualitative descriptive approach with library research methods or library studies. In this study, researchers do not have to go down to the field, all the research material can be presented or collected at the researchers' place in the library or library. In this study it was obtained that the school curriculum development procedures are structured by ignoring the compatibility between personal development and cognitive development simultaneously. Education is not merely a component but it nurtures the courage of the student to do something.